Systemic lupus erythematosus-related acute pancreatitis: An uncommon clinical manifestation (Indian Journal of Case Reports, 2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with diverse clinical manifestations, ranging from mild to life-threatening complications. Acute pancreatitis (AP) is a rare but serious manifestation of SLE, occurring in <2% of cases. SLE-related AP is often associated with high disease activity and can result in multiorgan dysfunction. We report the case of a 27-year-old female who presented with abdominal pain, joint pain, malar rash, pedal edema, and facial puffiness. Laboratory investigations revealed elevated serum amylase and lipase, with active SLE markers, including elevated antinuclear antibody and anti-dsDNA levels with hypocomplementemia. Contrastenhanced computed tomography abdomen confirmed acute interstitial edematous pancreatitis. The patient was also diagnosed with lupus nephritis. A diagnosis of SLE-related AP with concurrent lupus nephritis was established. The patient was managed with pulse corticosteroid therapy, immunosuppressive agents, and supportive measures, leading to significant clinical improvement. SLE-related AP is a rare life-threatening complication with multifactorial pathophysiology involving autoimmunity, vasculitis, and complement activation. This case highlights the importance of recognising AP as a rare but serious manifestation of SLE. Early diagnosis and prompt immunosuppressive therapy are crucial for improving outcomes.